Exploring the use of flow cytometry for understanding the efficacy of disinfection in chlorine contact tanks - Cheswick, Ryan; Nocker, Andreas; Moore, Graeme; Jefferson, Bruce; Jarvis, Peter (Elsevier, 2022)
A pilot scale chlorine contact tank (CCT) with flexible baffling was installed at an operational water treatment plant (WTP), taking a direct feed from the outlet of the rapid gravity filters (RGF). For the first time, disinfection efficacy was established by direct microbial monitoring in a continuous reactor using flow cytometry (FCM). Disinfection variables of dose, time, and hydraulic efficiency (short circuiting and dispersion) were explored following characterisation of the reactor's residence time distributions (RTD) by tracer testing. FCM enabled distinction to be made between changes in disinfection reactor design where standard culture-based methods could not. The product of chlorine concentration (C) and residence time (t) correlated well with inactivation of microbes, organisms, with the highest cell reductions (N/N0) reaching <0.025 at Ctx of 20 mg.min/L and above. The influence of reactor geometry on disinfection was best shown from the Ct10. This identified that the initial level of microbial inactivation was higher in unbaffled reactors for low Ct10 values, although the highest levels of inactivation of 0.015 could only be achieved in the baffled reactors, because these conditions enabled the highest Ct10 values to be achieved. Increased levels of disinfection were closely associated with increased formation of the trihalomethane disinfection by-products. The results highlight the importance of well-designed and operated CCT. The improved resolution afforded by FCM provides a tool that can dynamically quantify disinfection processes, enabling options for much better process control.
Keywords: Disinfection; Microorganisms; Chlorine; Drinking water; Flow cytometry